Characterization and Soil-Site Suitability Evaluation for Different Crops in Sarupathar Block of Golaghat District, Assam - Samiron Dutta (Journal of the Indian Society of Soil Science, 2022)
The present study was conducted in Sarupathar block of Golaghat district of Assam in order to characterize and evaluate the soils for their suitability for some important crops. Six representative soil profiles were collected covering the entire block area and soil-site characteristics were studied in detail. The soils were dark grayish brown (10YR 4/2) to very pale brown (10YR 7/3) in colour, sandy loam to clayey in texture with subangular blocky structure. Sand, silt and clay contents of the soils ranged from 14.4-35.6, 32.5-58.6 and 18.8-41.2%, respectively. The bulk density and particle density of the soils ranged from 1.14-1.38 and 2.10-2.39 Mg m-3, respectively. Organic carbon content of the soil varied from low to high (1.2-12.6 g kg-1). The cation exchange capacity of the soils was low [7.2-11.9 cmol(p+) kg-1] and base saturation ranged from 24.2-47.7%. Soils were classified as Oxyaquic Dystrudepts (P1, P2 and P3), Typic Dystrudepts (P4 and P5) and Aquic Dystrudepts (P6) at the subgroup level. The soils were rated as good except the soils of P4 which were rated as excellent as per the storie index rating. The soil-site suitability was evaluated for 17 crops (maize, pigeon pea, sunflower, sesame, potato, chilli, tea, arecanut, citrus, banana, lemon grass, pepper, vanilla, ginger, turmeric, cardamom and oil palm) following the simple limitation approach. Majority of the soils were found to be marginally suitable for the crops under the present condition. Some soils showed moderate suitability for crops like pigeon pea, tea, citrus, banana and oil palm. The soils can be improved to moderately suitable and in few cases to highly suitable class with specific interventions.